Highlights from Faraday Discussion 228: time resolved imaging of photo-induced dynamics. Issue 56 (23rd June 2021) - Dixit, Gopal; Kirrander, Adam
Abstract : A virtual Faraday Discussions meeting was held on the topic of 'Time resolved imaging of photo-induced dynamics'. This report covers the highlights of this meeting, including brief summaries of the papers discussed. Abstract : Summary of recent Faraday Discussions meeting (2021, vol. 228) on time resolved imaging of photo-induced dynamics. The meeting, originally scheduled to take place at IIT Bombay, took place online.